Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan - I'tamara, Izzatin; Hadi, Hafid Kholidi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This research aims to analyze the impact of motivation and working environment on employee performance. The study was held in Perumda Air Minum Tirta Lestari in Tuban Regency. Perumda Air Minum Tirta Lestari is a company that provides clean water services. This study uses a quantitative approach with probability sampling techniques. The sample used was 96 employees. Statistics are multilinear regressions using SPSS. The results show that motivation significantly impacts employee performance while work environment variables have no significant effect on employee performance. Companies must increase employee motivation by increasing motivational factors to maintain performance.